Low-temperature luminescence of nanosized SrAl2O4:Eu2+ - Nazarov, Mihail; Nazida, AwangNor; Calyn, S.; Aziz, N.; Ahmad-Fauzi, M. (Moldavian Journal of the Physical Sciences, 2012)
A stoichiometric SrAl2O4:Eu2 nanosized powder was synthesized by a combustion method using urea at 500°C and calcination at 1000ºC. The luminescence properties were investigated and two luminescence bands at 450 nm and 512 nm were observed at lower temperatures. This luminescence in the green region corresponds to transitions of Eu2 from 4f65d1 → 4f7. For the first time, an analysis of the electron-vibrational interaction and crystal field splitting of the Eu2 5d states has been performed for the considered system. The parameters of Stokes shift, Huang–Rhys factor, zero-phonon line position, and effective phonon energy were investigated and determined.